(untitled) (Konferensiyalar | Conferences, 2024)
The sonnet first appeared in poetry in Italy in the thirteenth century, during the height of the dolce still novo movement, which was sweeping the nation. Most people agree that the sonnet form was created by Giacomo da Lentino.